Neutral stability of the flow in a toroidal pipe - Canton, Jacopo; Örlü, Ramis; Schlatter, Philipp (Proceedings - 15th European Turbulence Conference, ETC 2015, 2015)
This work is concerned with the numerical investigation of the linear stability properties of the viscous, incompressible flow inside a toroidal pipe. A Hopf bifurcation is found and tracked in phase space, showing that the flow is modally unstable even at extremely low curvatures. The bifurcation and the eigenfunctions associated with it are analysed as a function of the two parameters governing the flow, i.e. the Reynolds number, Re, and the curvature, δ. For all curvatures, the critical Reynolds number is found to be about 3000.
CRIS-Team Scopus Importer:2023-03-21